Community structure of trees in Ayer Hitam Forest Reserve, Puchong, Selangor, Malaysia - Saari, Nurul Shida; Ibrahim, Faridah Hanum; Wan Mohd, Wan Razali; Abd. Kudus, Kamziah (Forestry Department Peninsular Malaysia, 2014)
A study on community structure of trees >1cm Dbh was conducted in Ayer Hitam Forest Reserve (AHFR), Puchong Selangor, Malaysia. AHFR is one of the three remaining forests left in the Klang Valley and it is the only logged-over lowland Dipterocarp forest in urban settings. The aim of this study was to describe the tree community structure through structural attributes which are stem density, basal area (BA), aboveground biomass (AGB) and height distribution. A total of 7359 stem ha-130.57 m2 ha-1 (BA) and 232.7 t ha-1 (AGB) were estimated for 1-ha. The most abundant species for Dipterocarpaceae and Non-Dipterocarpaceae were Hopea sulcata Symington and Agrostistachys longifolia (Wight) Benth. (Euphorbiaceae), respectively. This study shows that AHFR is recovering but slowly and has good regeneration potential.